Perbandingan Loading Cairan dan Menurunkan Gas Inhalasi dengan Pemberian Ephedrin untuk Pencegahan Hipotensi - M.Rossy Rakasiwi; Nurul Istiqomah; Kusumaning Tyas (Jurnal Rumpun Ilmu Kesehatan, 2022)
Background: General anesthesia is the act of administering a combination of drugs during surgery with the aim of reducing consciousness and eliminating pain in the patient. There are 2.5% of patients experiencing intra-anesthesia complications including hypotension.Objective: To determine the comparison of giving fluid loading and reducing inhaled gas with giving ephedrine to prevent hypotension in patients in central surgery installations.Research Metod: Quantitative method with experimental research type with quasi-experiment. This research used a Pretest-Posttest Two Group Design with 22 respondents.Research Result: Based on test statistics, it is known that the results of the Independent Sample T Test data analysis test show a P value (>0.05), namely H0 is accepted. Based on this test, it was concluded that there was no significant relationship between administering fluid loading and reducing inhaled gas with administering ephedrine to prevent hypotension.Conclusion: Based on this research, researchers are more effective in using fluid loading and reducing inhaled gas than administering ephedrine in the ETT technique for general anesthesia.